The use of discontinuous PEEK/carbon fiber thermoplastic moulding compounds for thick-section componentry - Samuel Erland (Taylor & Francis Group, 2019)
The hot-pressing of discontinuous fiber moulding compounds (DFMCs) is an established way of forming geometrically complex components, however, it is not a simple process. Rapid and irreversible cure cycles hinder the use of thermoset resins, and thermoplastic resins offer inferior mechanical performance. The recent availability of DFMCs utilising a Polyether Ether Ketone (PEEK) matrix offer an alternative, combining the usability of thermoplastics with significantly enhanced mechanical properties. A novel manufacturing approach is proposed and investigated, in which virgin material is consolidated into multiple ‘pre-charges’ prior to pressing the final component, combating the limitations of DFMCs; loft, voidage and fiber orientation. Short beam shear tests were employed to assess the mechanical implications of laminating DFMCs, demonstrating minimal differences to a standard sample. Three-point bend tests assessed rudimentary orientation of fiber bundles, showing significantly improved mechanical performance at the cost of toughness. A novel method to determine the interlaminar shear modulus is also presented and successfully validated.